2020
DOI: 10.54692/ajss.2020.04031100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Machiavellian Leadership to Counterproductive Work Behavior with Mediating Mechanism of Justice Perceptions: Evidence from Tanner Sector of Pakistan

Abstract: The aim of this study is to evaluate the relationship between Machiavellian leadership and counterproductive work behavior (CWB) in tanners sector of Pakistan. The study also investigated the mediating role of justice perceptions in these relationships. Data were collected from 353 respondents by using self-administered questionnaires from tanners sector of Pakistan. Data were analyzed through Structure equation modeling and test the hypothesized relationships. Quantitative results showed the existence of Mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The overall organizational justice has been illustrated in previous studies that how employees perceive the procedures are fair at workplace as it is linked with the perception of an individual, so therefore it is crucial for organizational workplace as it predicts number of outcomes. The research studies has depicted that overall organizational justice influence the CWB and mediates the relationship between Machiavellianism and CWB (Younus et al, 2020). In this investigation, the organizational structure was found to have a positive and significant impact on procedural justice, informational justice, and distributive justice.…”
Section: Moderation Role Of Overall Organizational Justicementioning
confidence: 55%
See 1 more Smart Citation
“…The overall organizational justice has been illustrated in previous studies that how employees perceive the procedures are fair at workplace as it is linked with the perception of an individual, so therefore it is crucial for organizational workplace as it predicts number of outcomes. The research studies has depicted that overall organizational justice influence the CWB and mediates the relationship between Machiavellianism and CWB (Younus et al, 2020). In this investigation, the organizational structure was found to have a positive and significant impact on procedural justice, informational justice, and distributive justice.…”
Section: Moderation Role Of Overall Organizational Justicementioning
confidence: 55%
“…According to the outcomes of the study, Machiavellianism is a strong predictor of CWB, and the impression of justice has a negative impact on CWB. The study discovered that justice perception influences Machiavellianism leadership and CWB (Younus et al, 2020). The research study reported PO fit positively significantly related to psychological ownership.…”
Section: Mediating Role Of Person-organization Fitmentioning
confidence: 81%
“…Moreover, previous studies found that Machiavellianism is positively related to counterproductive work behaviors and causes a range of undesirable work outcomes (Stoica, 2021;Wille et al, 2022;Elsawyet al, 2022;Barry, 2020;Younus et al, 2020). Additionally, Machiavellianism associated positively with burnout and its components (emotional exhaustion, depersonalization, and diminished personal accomplishment), and negatively with general job satisfaction, life satisfaction, ethical behaviors, organizational commitment, job satisfaction, whistleblowing actions which are beneficial for the organization to achieve its goals, workplace spirituality, Organizational Trust Grover & Furnham, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the actual behavior of Machiavellian individuals in the workplace remains questionable. Delving deeper into the study of the manifestations of high Machiavellianism in individual behavior is intriguing because current research is predominantly focused on its negative effects on work, such as the tendency for fraudulent behavior (Nurjanah & Purnamasari, 2020) and counterproductive work behavior (Yuliana & Suyasa, 2018;Younus et al, 2020).…”
Section: Introductionmentioning
confidence: 99%